PENGARUH KOMUNIKASI, MOTIVASI KERJA DAN ETOS KERJA TERHADAP KINERJA KARYAWAN DI PTPN III MEDAN - Yosafat Rizal Simanjuntak; Elfrans Fernando Nainggolan; Grecca Helena Sipayung; Ina Namora Putri Siregar; Ainul Mardhiyah (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This acquisition aims to generate a relationship between a free variable to a partially and simultaneously bound variable which consists of a communication-free variable, a work motivation and a work ethos and a performance-bound Variable. This research has a quantitative approach that is capable of delivering maximum results in this study, then is described in a comprehensive way with the number of objects studied as many as 80 employees with methods and approaches of data collection more appropriate such as interviews and discussions through questionnaires. As for the results of this study partially tested and simultaneously all free variables against the bound variables have a very strong influence therefore further research needs to make changes to the variables to be investigated.